What Will be the Impact of Transposing Directive (EU) 2022/2464 of the European Parliament and of the Council in Romania? - Ramona-Ionela Haraguș; Attila Szora Tamaș (Revista de Studii Financiare)
Directive (EU) 2022/2464 of the European Parliament and of the Council of 14 December 2022, amending Regulation (EU) No. 537/2014, Directive 2004/109/EC, Directive 2006/43/EC and Directive 2013/34/EU as regards sustainability reporting by undertakings, the L-series, no. 322, of 16 December 2022, was published in the Official Journal of the European Union. The purpose of this research is to establish, through a conceptual approach, which are the aspects regulated by the European Directive transposed, which will be the normative acts subject to modification/completion following the transposition of Directive (EU) 2022/2464 in Romania, as well as the provisions regarding the audit of the annual financial situations. The adoption of the Directive on social and environmental responsibility (CSRD) aims to improve the way in which entities report social and environmental information in order to increase standardisation, consistency and comparability of non-financial information submitted across the Union.